Towards hybridization of ultra-high molecular weight polyethylene composites by thermally sprayed alumina: Feasibility and bond strength assessment. (March 2023) - Bensaada, R.; El Malki Alaoui, A.; Darut, G.; Costil, S.; Arrigoni, M.
Graphical abstract: Highlights: UHMWPE Tensylon is successfully thermaly spraying coated by 200 µm thick Alumina by using an intermediate Zn layer. LASAT method has been successfully experienced to assess the coating adhesion at high strain rates. The obtained hybridized structure reduces the rear face velocity under shock by more than half, very effective for impact resilience. Abstract: Composite materials are increasingly inescapable in engineered systems in various industrial fields, given their high strength to weight ratio for increasing autonomy, reducing energy consumption and enhancing mechanical strength of high added value products. However, their out-of-plane resistance could be improved by multimaterial assembly for structural hybridization. The purpose of this study is to explore the possibility of upgrading the shock resistance of UHMWPE Tensylon® by alumina coating. Thermal spraying was used for alumina deposition on UHMWPE and bond strength assessment of the obtained assembly was performed by Laser Adhesion Test (LASAT). During experiments, free surface velocities of specimens were recorded by the use of Photonic Doppler Velocimetry (PDV) allowing relevant observations complementary to optical observations. From the PDV analysis and cross section observations by microscopy, a diagnostic of the decohesion of the interface is proposed. The study shows the possibility of assembling alumina on UHMWPE to strengthen its shock resistance and makes now possible the improvement of the study of deposition process parameters thanks to LASAT evaluations.